Relevance of cardiac imaging in the evolving landscape of infective endocarditis management - Alice Haouzi; Mohamed Khayata; Bo Xu (Therapeutic Advances in Cardiovascular Disease)
Infective endocarditis (IE) is an increasingly recognized condition with high morbidity. Patients with atypical symptoms, culture-negative infections, and prosthetic cardiac devices and implants represent challenging populations to evaluate and manage. Recent major society guidelines have recommended the appropriate incorporation of multimodality imaging in the evaluation of these more complex IE cases. This article draws on the available literature regarding the different cardiac imaging modalities and discusses the role of multimodality imaging in IE.